2012
DOI: 10.1371/journal.pone.0044843
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis bHLH100 and bHLH101 Control Iron Homeostasis via a FIT-Independent Pathway

Abstract: Iron deficiency induces a complex set of responses in plants, including developmental and physiological changes, to increase iron uptake from soil. In Arabidopsis, many transporters involved in the absorption and distribution of iron have been identified over the past decade. However, little is known about the signaling pathways and networks driving the various responses to low iron. Only the basic helix–loop–helix (bHLH) transcription factor FIT has been shown to control the expression of the root iron uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
138
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(146 citation statements)
references
References 22 publications
8
138
0
Order By: Relevance
“…Surprisingly, IRT1 amounts in CHX-treated Col-0 were slightly elevated in comparison to the corresponding control, suggesting that factors with a high turnover rate might negatively influence IRT1 stability. Similar effects were recently reported for the transcriptional regulation of the IRT1 gene (Sivitz et al, 2012). In the snx1-2 and snx triple mutants, a strong reduction in IRT1 levels was observed after CHX treatment.…”
Section: Irt1 Protein Stability Is Decreased In the Absence Of Snx Prsupporting
confidence: 87%
“…Surprisingly, IRT1 amounts in CHX-treated Col-0 were slightly elevated in comparison to the corresponding control, suggesting that factors with a high turnover rate might negatively influence IRT1 stability. Similar effects were recently reported for the transcriptional regulation of the IRT1 gene (Sivitz et al, 2012). In the snx1-2 and snx triple mutants, a strong reduction in IRT1 levels was observed after CHX treatment.…”
Section: Irt1 Protein Stability Is Decreased In the Absence Of Snx Prsupporting
confidence: 87%
“…Abundance under control conditions increases to the right in the plots. As expected, after 2 d of Fe deficiency, FER1 expression was decreased, while PYE, BHLH38, and BHLH100, markers for plant Fe deficiency (Long et al, 2010;Sivitz et al, 2012), were up-regulated. Generally, a good correlation was observed between protein and mRNA abundance.…”
Section: Fe Deficiency Affects Photosynthetic Electron Transport Primsupporting
confidence: 81%
“…1A), further validating the up-regulation of BTS under iron deficiency. Microarray analysis has revealed that apart from roots, BTS is also expressed in shoots in Arabidopsis (Sivitz et al, 2012). To characterize BTS expression in the shoot and during reproductive growth, we performed GUS staining on young seedlings and mature plants.…”
Section: Bts Is Expressed Throughout Plant Developmentmentioning
confidence: 99%
“…FIT acts in concert with two other bHLH proteins (Yuan et al, 2008), ETHYLENE INSENSITIVE3 and ETHYLENE INSENSITIVE3-LIKE1 , and is posttranslationally regulated by the presence of nitric oxide via 26S proteasomedependent degradation (Meiser et al, 2011;Sivitz et al, 2011). A FIT-independent iron homeostasis pathway has also been identified involving bHLH100 and bHLH101 (Sivitz et al, 2012). Recently, it has been shown that root exudates including phenolics and riboflavin derivatives function as iron-binding compounds in Arabidopsis and Medicago truncatula, similar to those in the chelation-based Strategy II response.…”
mentioning
confidence: 99%